(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study aims to investigate how FinTech can drive financial inclusion in rural India by analyzing rural consumers’ financial behavior and the factors influencing FinTech adoption. Additionally, the research explores socio-cultural norms, technological limitations, and trust issues in relation to FinTech platforms like PhonePe and Google Pay. Methods: This study employed an empirical, quantitative methodology, data were collected via a standardized online questionnaire from 257 respondents, focusing on financial behavior, digital financial literacy, and overall financial inclusion. Analysis of this data by implying ANOVA and Regression analysis revealed critical insights into the strategies, impacts, and challenges encountered by FinTech initiatives. Results: The findings reveal that societal norms often overlook the gender gap and limit women’s involvement in financial decision-making. Yet, FinTech is beginning to address this issue with its advanced technologies. The pervasive lack of digital and financial literacy in rural regions is a serious obstacle to the broad adoption of m-transactions. Moreover, the uptake of FinTech app solutions is largely dependent on factors such as system accessibility and ease of use. While financial services have become more available and are contributing to economic empowerment, persistent issues like poor digital infrastructure and regulatory constraints continue to hinder progress. Conclusion: Investors, regulators, and legislators may use the study’s important insights to develop best practices that enhance FinTech’s social and financial benefits. Additionally, it outlines how financial institutions might manage cross-border transactions for low-income populations and makes suggestions for mobile service providers to provide more reasonably priced services.